INFLUENCE OF ORGANIZATIONS FOR THE RURAL DEVELOPMENT: THE CASE OF SALINAS, SAN LUIS POTOSÍ - Pérez-Hernández, Luz María; Figueroa-Sandoval, Benjamín; Díaz-Puente, José María; Almeraya-Quintero, Silvia Xochilt (Revista Mexicana de Ciencias Agrícolas, 2018)
The organization is considered as a strategic element in the development of a rural locality, because through it higher benefits are obtained, it allows people to develop their skills and promotes projects within the communities. However, it is common that rural areas have a dismantled association network that limits those possibilities. For that reason, the causes of low society’s participation in organized groups and the problems faced by organizations were tried to know; based in a case study in the municipality of Salinas, San Luis Potosí, Mexico, in 2009. The aim of this paper is to identify the reasons why an organization does not have an impact on the municipality, allowing the formulation of a strategy and make it be an engine of development in the territory. The results indicate that most people do not participate in any organization even when they like working in groups. In general, organizations are finding it difficult to make arrangements and meet commitments. Formal organizations in the municipality include economic and representative organizations. Both have internal problems related to lack of funding, poor training and lack of commitment of the group; these elements have not allowed their consolidation and their participation in municipality’s development.
Keywords: objectives; participation; territory